Reagents and mechanism in organic synthesis: Problem solving approach - Jena, Satyaban; Rout, Laxmidhar (New Delhi: Indu book services, 2024)
There are eight chapters in the book starting from scratch to complex level. Chapter 1 is started with problem on oxidizing reagents including chiral oxidizing reagent. Chapter 2 deals with problems on achiral and chiral reducing reagent, whereas chapter 3 is related to problems on protecting and protecting reagent. Chapter 5 covers with problems on reagent for alkylation, acylation, alkylation, acylation, formylation and propargylation. Chapter 5 is related to problems on reagent related to halogenation reaction. Chapter 6 covers the problems on reagent related to ylides. Chapter 7 contain other miscellaneous and important reagents not covered on previous chapters. The final chapter 8 is designed based on the knowledge of all previous chapters. This last chapter contain the road map problems related previous chapters. The book contains more than 974 problems and 572 pages. The book will be valuable for MSc, BSc (Hons), JAM, GRE, GATE, CSIR-NET, IISc, IIT, IISER, TIFR, NIT, and all universities.
Includes appendix
Keywords: Organic synthesis -- Reaction mechanisms -- Reagents - Chemistry